Analysis of Community Perceptions on Halal Certification for Packaged Food Products - Saragih, Dini Setiana; Syahbudi, Muhammad; Bi Rahmani, Nur Ahmadi (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2024)
This study provides valuable insights into the perceptions of Silou Paribuan Village residents regarding halal certification, enhancing the understanding of consumer behavior in rural settings. The research analyzes how these residents perceive halal certification when purchasing packaged food products. A qualitative descriptive method was used, drawing on consumer behavior theory and Sharia economic principles to explore these perceptions. Data was gathered through interviews and surveys, with 96 individuals selected from a total population of 2,375 using the Slovin formula with a 10% margin of error. Simple random sampling was employed to ensure representative participation. The data was collected via a questionnaire that utilized a Likert scale to gauge respondents' attitudes. The analysis applied consumer perception theories, including attribution, gestalt, product quality, and marketing communications. The results revealed that the perception of halal certification among Silou Paribuan Village residents is generally positive, with an average score of 74%. Most respondents recognized the importance of halal certification when choosing packaged food products. However, the study's focus on a single village may limit the generalizability of its findings to broader populations or different cultural contexts.